Diplomacy theory and practice - Berridge, Geoff R. (Palgrave Macmillian, 2022)
This fully revised and expanded sixth edition of Diplomacy, written by an internationally respected researcher and teacher of the subject, is richly illustrated with examples from the worlds of health and commerce as well as high politics. The instances included are mostly contemporary, but considerable historical background to the diplomatic methods themselves is always provided. Among other features, new to this edition is a list of topics for seminar discussion or essays, as well as annotated further reading at the end of each chapter. Following a chapter on the foreign ministry, Part I of this book deals with the art of negotiation (prenegotiations, around-the-table negotiations, diplomatic momentum, packaging agreements, and following up); Part II covers conventional modes of diplomacy (embassies, telecommunications, consulates, secret intelligence by 'legals', conferences, summits, and public diplomacy); and Part III examines diplomacy in hostile circumstances (embassy substitutes such as representative offices and interests sections, special missions, and mediation). Students and educators of diplomacy will find much of value in the latest edition of this highly regarded and much-cited textbook.